Vegetative survival of some wall and soil blue-green algae under stress conditions - Gupta, S; Agrawal, S C (Folia microbiologica, 2008)
Lyngbya major (a wall alga), survived throughout year, maximally to >80 % at atmospheric temperature (AT) of 17-36 degrees C and relative humidity (RH) 60-100 % in rainy and spring seasons, but the survival was 43-64 % in winter when AT decreased to 5 degrees C and RH was 65-98 %, and 15-23 % in summer when AT reached 48 degrees C and RH was 23-60 %. All soil algae (Lyngbya birgei, Aphanothece pallida, Gloeocapsa atrata, Oscillatoria subbrevis, O. animalis) survived >90 % in rainy season when soil moisture content (SMC) was 89-100 %. Lowering of SMC to a minimum of 55 % in spring and 39 % in winter led L. birgei, O. subbrevis and O. animalis to survive from 75, 66, and 65 %, respectively, in spring and 12, 14, and 20 % in winter, and A. pallida and G. atrata not at all in both seasons. All soil algae did not survive in summer when SMC was 12-30 %. Myxosarcina burmensis survived only in rainy and spring seasons when pond water temperature (PWT) was 19-25 degrees C and 18-26 degrees C, respectively, and not in winter and summer when PWT was 2-14 degrees C and 25-36 degrees C, respectively. L. major and A. pallida survived almost equally well under both submerged and air-exposed conditions for 15 d but less if submerged for more time than air-exposed on moist soil surface, while L. birgei, G. atrata, O. subbrevis, and O. animalis survived submergence in liquid medium better and longer than air-exposure on moist soil surface. Pond alga M. burmensis survived submergence better than air-exposure, true to its aquatic habitat. All algae survived less and died without forming any resistant cells when exposed to physical and physiological water stress (imposed by growing them on highly agarized media or in salinized liquid media), light stress (at 0, 2 and 10 micromol m(-2) s(-1) light intensity) or following UV shock (0.96-3.84 kJ/m(2)). A. pallida and G. atrata cells did not divide on 8 % agarized solid media, in > or =0.3 mol/L salinized liquid media, and in darkness. The presence of sheath over L. major and L. birgei filament cells and mucilage cover over A. pallida and G. atrata cells protect them against physical desiccation to some extent but not against UV shock.
Keywords: Temperature; Cyanobacteria; Ecosystem; mikrobiální viabilita; Soil Microbiology; sinice; Soil; Stress, Physiological; ultrafialové záření; Microbial Viability; roční období; Seasons; vlhkost; Ultraviolet Rays; ekosystém; půdní mikrobiologie; Humidity; teplota; půda; fyziologický stres